Project planning and management: A text of principles and practice with a case - Ruzibuka, J. E. M; Rutebinga, P. R (Research, Information and Publication Department, 2025)
The pace of development in developing countries including Tanzania requires the availability of enough and well trained officers and managers in the field of project planning and project management. This is a challenge to most of the training institutions in these countries to be able to cope with this pressing need for qualified project personnel and to produce the required textbooks and teaching materials relevant to their own countries' economies and project environments, as well as closing the gap which created by lack of foreign exchange to import text books for use in training. This books is meant to meet the above needs and is an outcome of the authors' long experiences in training project planning and management in both long courses and short courses at the Institute of Development Management (IDM) Mzumbe, Morogoro, Tanzania. This book is expected to be of great use to the undergraduate and graduate students in this subject in 'institutions of higher learning and to the vast number of economic planners, engineers, agronomists etc. who are involved in different project works as practitioners in government ministries, Departments, banks, cooperatives and parastatal organizations at different levels. This book will also prove of great use to many academicians in institutions of higher learning. Given the varied and wide range of potential users of this backed the with authors’ case have covered thoroughly the following areas studies: - Pre-Investment planning of projects and their management planning. - Investment stage planning of projects and management. - Post-Investment Planning, Organization of the Projects.